2006
DOI: 10.1242/dev.02255
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty proteins are in vivo targets of Corkscrew/SHP-2 tyrosine phosphatases

Abstract: , §Drosophila Corkscrew protein and its vertebrate ortholog SHP-2 (now known as Ptpn11) positively modulate receptor tyrosine kinase (RTK) signaling during development, but how these tyrosine phosphatases promote tyrosine kinase signaling is not well understood. Sprouty proteins are tyrosine-phosphorylated RTK feedback inhibitors, but their regulation and mechanism of action are also poorly understood. Here, we show that Corkscrew/SHP-2 proteins control Sprouty phosphorylation and function. Genetic experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 54 publications
1
52
0
1
Order By: Relevance
“…3F). Prior studies have shown that Shp2 promotes receptor tyrosine kinase signaling by inactivating Sprouty 1, a feedback inhibitor of the Erk pathway, in Drosophila (21,22). To test whether Sprouty 1 is an Shp2 target in INS-1 832/13 cells, we first determined whether Shp2 associated with Sprouty 1 protein by coimmunoprecipitation.…”
Section: Shp2 Deficiency Attenuates Signaling Through Akt/foxo1 and Erkmentioning
confidence: 99%
“…3F). Prior studies have shown that Shp2 promotes receptor tyrosine kinase signaling by inactivating Sprouty 1, a feedback inhibitor of the Erk pathway, in Drosophila (21,22). To test whether Sprouty 1 is an Shp2 target in INS-1 832/13 cells, we first determined whether Shp2 associated with Sprouty 1 protein by coimmunoprecipitation.…”
Section: Shp2 Deficiency Attenuates Signaling Through Akt/foxo1 and Erkmentioning
confidence: 99%
“…Also commonly noted is the binding of SOS to FRS2 via GRB2 and the subsequent activation of the RAS-MAP kinase pathway (ibid) together with CBL induced degradation (Dailey et al, 2005). It is also known that SHP2 can induce a dephosphorylation of SPRY (Jarvis et al, 2006;Hanafusa et al, 2004) and that SPRY associates with GRB2 (Thisse and Thisse, 2005) plus CBL (Wong et al, 2001). Signal attenuation due to SRC binding FRS2 has also been reported, along with the observation that SPRY is a direct physiological substrate for SRC (Li et al, 2004).…”
Section: Model Motivationmentioning
confidence: 94%
“…The Src family of kinases is likely responsible for phosphorylation of SPRY at this conserved tyrosine, while Shp2 phosphatase is involved in dephosphorylating this critical residue [119][120][121][122] (Fig. 10).…”
Section: Sprouty Proteins and Rtk Signalingmentioning
confidence: 99%